FORMULATION AND BIOPHARMACEUTICAL EVALUATION OF SUSTAINED RELEASE PELLETS OF BOSENTAN BY PANCOATING METHOD - REDDY, GVRAMI; V., PALLAVI; P., RAKESH; NADENDLA, RAMARAO (International Journal of Applied Pharmaceutics, 2024)
Objective: The aim of the present study was to formulate sustained-release pellets of bosentan by eudragit RL 100 and RS 100, which are the polymers used in the pan coating technique. Methods: The sustained release pellets of bosentan were formulated by pan coating method. The drug was coated on nonpareil seeds along with EudragitRL100 by solution layering technique. Drug-loaded pellets were coated with EudragitRS100. The prepared pellets were evaluated for moisture content, drug content, particle size, and in vitro drug release. Stability studies were carried out on the optimised formulations for a period of 6 mo. Results: The drug content was in the range of 98.89±0.32. The mean particle size of the drug-loaded pellets was in the range of 835 μm. The drug release rate decreased as the concentration of eudragit increased in the pellet formulations. Among the prepared formulations, PC 4 showed 89.35±0.52 drug release in 12 h from a good linear relationship was established between model-independent approaches (T25%, T50%, and T100%) and weight gain in coating. This indicated the possibility of extending the drug release by increasing the weight gain in the coating, and hence, it was proposed to extend the drug release for 24 h. From the prepared pellets, the optimised formulation PC 12 showed a 100.02±0.03 drug release in 24 h. Furthermore, these pellets were filled into capsules and compared the dissolution studies. The compatibility between drugs and polymers in the drug-loaded pellets was confirmed by DSC and FTIR studies. Stability studies indicated that the pellets were stable. Conclusion: The prepared pellets were capable of releasing the drug for 24 h to treat the Pulmonary Arterial Hypertension.